Exploring the role of regional research and development support in enhancing foreign investment in Poland: A spatial analysis perspectives - Wibisono, Eristian (European Spatial Research and Policy, 2024)
This study aims to investigate the nature and drivers of foreign investment in 16 regions of Poland. Using a spatial analysis approach, the study examines the spatial characteristics of the factors that influence foreign investment, namely labour and research and development (R&D) support. The results of the first analysis indicate strong spatial characteristics and interregional correlations in the observed variables, although they are not characterised by spatial dependence. The regression analysis results show that R&D expenditure significantly supports the enhancement of foreign investment alongside the labour factor, which has a more substantial impact.